2021
DOI: 10.1002/jso.26418
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing the impact of tumor size on operative approach in adrenocortical carcinoma

Abstract: Background Adrenocortical carcinoma (ACC) is often a contraindication to minimally invasive adrenalectomy (MIA). We used an administrative data set to analyze postoperative outcomes. We hypothesized that small tumors would have better short‐ and long‐term outcomes, independent of the operative approach. Methods The National Cancer Database (2010–2016) identified patients with ACC who underwent adrenalectomy. Tumors were grouped: <5 cm (n = 125), 5–10 cm (n = 431), and >10 cm (n = 443). The primary and secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…It is still a matter of debate whether LA for large adrenal tumors is safe and feasible. Several studies show that, especially in case of PCC, large adrenal lesions are associated with higher rates of conversion and blood loss, longer operative time, and hospital stay [10][11][12][15][16][17][18][19][20], while others failed to find a correlation between tumor size and perioperative outcomes [21][22][23]. Laparoscopic approach was not identified as a variable influencing perioperative outcomes in recent studies [36][37][38][39]; furthermore, Kiernan et al [40] reported how the open technique significantly increased intra-and postoperative hemodynamic instability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is still a matter of debate whether LA for large adrenal tumors is safe and feasible. Several studies show that, especially in case of PCC, large adrenal lesions are associated with higher rates of conversion and blood loss, longer operative time, and hospital stay [10][11][12][15][16][17][18][19][20], while others failed to find a correlation between tumor size and perioperative outcomes [21][22][23]. Laparoscopic approach was not identified as a variable influencing perioperative outcomes in recent studies [36][37][38][39]; furthermore, Kiernan et al [40] reported how the open technique significantly increased intra-and postoperative hemodynamic instability.…”
Section: Discussionmentioning
confidence: 99%
“…Several risk factors for perioperative morbidity after LA have been identified [10][11][12][13][14][15], but only few studies have investigated specific predictors of morbidity after LA for PCC [16][17][18][19][20]. In particular, the role of PCC size, one of the most frequently reported predictor of perioperative complications, is controversial [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, tumor size alone was not a risk factor for margin positive resection. Prior work by Hue et al similarly showed that, among MIS‐resected ACC, local invasion and conversion to OA were more powerful predictors of PM than tumor size 16 . These data challenge the notion that adrenal nodules beyond a certain diameter must be approached via OA resection.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, Cord S et al suggested that tumor size is a useful way for predicting the likelihood of ACC [ 27 ]. Jonathan J et al implied that tumor size of ACC ≥ 5 cm increased the margin positivity rate and affected the prognosis of ACC patients [ 28 ].…”
Section: Discussionmentioning
confidence: 99%